Cup-cone structure in spallation of bulk metallic glasses. (1st October 2019) - Tang, X.C.; Li, C.; Li, H.Y.; Xiao, X.H.; Lu, L.; Yao, X.H.; Luo, S.N.
Abstract: A special spallation morphology in bulk metallic glass, named as the "cup-cone" structure, is of particular interest since it manifests a unique "ductile–brittle" transition. To gain insights into the underlying mechanism for the formation of a cup-cone structure, we conduct planar impact experiments at various impact velocities, as well as finite element method analysis. Spall strength increases with increasing impact velocity. Scanning electron microscopy and X-ray computed tomography are performed on postmortem samples to characterize cup-cone structures; their average size and spacing decrease as impact velocity increases, and they dominate fracture morphology at high impact velocities. Cups and cones are generally distributed on the side away from and on the side closer to the target free surface, respectively. The initial nucleation sites of voids become the conical vertices of cup-cones, and the subsequent nucleation sites form along the conical surface and coalesce into the cracks and fracture surfaces. Graphical abstract: Image 1